Killing commendatore - Murakami, Haruki 1949- (Alfred A. Knopf, 2018)
"The much-anticipated new novel from the internationally acclaimed, best-selling author of 1Q84 and Colorless Tsukuru Tazaki and His Years of Pilgrimage, Killing Commendatore is an epic tour de force of love and loneliness, war and art...as well as a loving homage to The Great Gatsby...and a stunning work of imagination from one of our greatest writers"...
"Originally published in Japan as KISHIDANCHO-GOROSHI DAI-ICHI-BU ARAWARERU IDEA HEN and KISHIDANCHO-GOROSHI DAI-NI-BU UTSUROU METAFUA HEN by SHINCHOSHA Publishing Co., Ltd., Tokyo in 2017" ... Verso title page
Keywords: Fantasy fiction; FICTION / Literary / bisacsh; FICTION / Historical / bisacsh; Portrait painters -- Fiction; Painting, Japanese -- Fiction; FICTION / Literary; FICTION / Historical